Defect Heterogeneity in Monolayer WS2 Unveiled by Work Function Variance - Wang, Xinyun; Dan, Jiadong; Hu, Zhenliang; Leong, Jin Feng; Zhang, Qi; Qin, Ziyu; Li, Shisheng; Lu, Junpeng; Pennycook, Stephen J; Sun, Wanxin; Sow, Chorng Haur (Chemistry of materials, 2019)
Defects are commonly found in two-dimensional (2D) transition-metal dichalcogenide (TMD) materials. Such defects usually dictate the optical and electrical properties of TMDs. It is thus important to develop techniques to characterize the defects directly with good spatial resolution, specificity, and throughput. Herein, we demonstrate that Kelvin probe force microscopy (KPFM) is a versatile technique for this task. It is able to unveil defect heterogeneity of 2D materials with a spatial resolution of 10 nm and energy sensitivity better than 10 meV. KPFM mappings of monolayer WS2 exhibit interesting work function variances that are associated with defects distribution. This finding is verified by aberration-corrected scanning transmission electron microscopy and density functional theory calculations. In particular, a strong correlation among the work function, electrical and optical responses to the defects is revealed. Our findings demonstrate the potential of KPFM as an effective tool for exploring the intrinsic defects in TMDs.